Sand fraction, foraminifer isotopic composition and foraminifer element ratios of ODP Site 198-1209 sediments, Shatsky Rise - Andrea Dutton; Kyger C Lohmann; R Mark Leckie (PANGAEA, 2005)
Stable oxygen and carbon isotope measurements (d18O and d13C) of planktonic and benthic foraminifers were conducted to assess the temperature history and circulation patterns over Shatsky Rise during the Paleocene and Eocene. A record of Mg/Ca for benthic foraminifers was also constructed in order to better determine the relative influence of temperature, salinity, and/or ice volume upon the benthic d18O record. Isotopic analyses were carried out on several planktonic taxa (Acarinina, Morozovella, Globigerinatheka, Praemurica, and Subbotina) as well as several benthic taxa (Nuttalides, Oridorsalis, Cibicidoides, Gavelinella, and Lenticulina). Elemental analyses were restricted to three benthic taxa: Nuttalides, Oridorsalis, and Gavelinella. All specimens were derived from the composite sediment section recovered from Ocean Drilling Program Site 1209 on the Southern High of Shatsky Rise.
Supplement to: Dutton, A et al. (2005): Data report: Stable isotope and Mg/Ca of Paleocene and Eocene foraminifers, ODP Site 1209, Shatsky Rise. In: Bralower, TJ; Premoli Silva, I; Malone, MJ (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 198, 1-19, https://doi.org/10.2973/odp.proc.sr.198.119.2005